Participation of women in politics: A study of local councils and state legislature - Lalchatuanthangi (2016)
Under the Sixth Schedule, the Lushai Hills District Council and Pawi-Lakher Regional Council (PLRC) were created on April 25, 1952, and April 23, 1953, respectively. The Lushai Hill District (Chieftainship Abolition) Act, 1952, was passed by the Assam Legislative Assembly on January 1, 1953. According to the Act, all the existing Chiefs as on April 25, 1952, within the Lushai Hill District were to be abolished. With the formation of the District Council the whole administrative set-up of the Lushai Hills was changed enabling the people to participate in the formation of the Government through adult franchise. Chieftainship was replaced by the Village Councils with much reduced powers. In 2014, the Lushai Hills District (Village Councils) Amendment Act was passed; this amendment changed the term of the Village Council member from three years to five years. Moreover, reservation of seats for women in the Village Council was also enacted by amending the Act. This article, traces the historical development of women's participation in politics, especially in Village Councils in Mizoram. - Reproduced.
Keywords: Women in politics